PENGARUH REGULASI EMOSI DAN DUKUNGAN SOSIAL KELUARGA TERHADAP RESILIENSI AKADEMIK SISWA - Ananda Putri; Nefi Darmayanti; Asih Menanti (Institut Agama Islam Negeri (IAIN) Manado, 2023)
ABSTRACTThis study aims to determine the effect of emotional regulation and family social support on student academic resilience at MAS Raudhatul Akmal. The subjects in this study were 113 students. Methods of data collection using simple random sampling technique. Academic resilience is measured by a scale of aspects of academic resilience according to Cassidy there are 18 valid items and emotional regulation is measured by a scale of aspects of emotional regulation according to Gross, J.J. & Thompson there are 13 valid items, while family social support is measured by a scale of aspects of family social support according to House there are 28 valid items. Data analysis with multiple regression. The results showed that there was an effect of emotional regulation and family social support on academic resilience with an F count of 19,207. Multiple regression test results 0.000<0.05, and R2 = 0.259. There is an effect of family social support on academic resilience of rx2y 0.333 with p<0.05, and multiple regression test 0.027<0.05. There is an effect of emotional regulation on academic resilience with an rx1y value of 0.474 with p<0.05, as well as a multiple regression test with a result of 0.000<0.05.Keywords: Emotion Regulation, Family Social Support, Academic Resilience ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh regulasi emosi dan dukungan sosial keluarga terhadap resiliensi akademik siswa di MAS Raudhatul Akmal Kecamatan Batang Kuis Kabupaten Deli Serdang. Subjek dalam penelitian ini 113 siswa. Metode pengumpulan data menggunakan teknik simple random sampling. Resiliensi akademik diukur dengan skala aspek-aspek resiliensi akademik menurut Cassidy ada 18 item valid dan regulasi emosi diukur dengan skala aspek-aspek regulasi emosi menurut Gross, J.J. & Thompson ada 13 item valid, sedangkan dukungan sosial keluarga diukur dengan skala aspek-aspek dukungan sosial keluarga menurut House ada 28 item valid. Analisa data dengan regresi berganda. Hasil penelitian menunjukkan ada pengaruh regulasi emosi dan dukungan sosial keluarga terhadap resiliensi akademik dengan nilai F hitung 19.207. Hasil uji regresi berganda 0,000 < 0,05, dan R2 = 0,259. Ada pengaruh dukungan sosial keluarga terhadap resiliensi akademik sebesar rx2y 0.333 dengan p < 0.05, serta uji regresi berganda 0,027 < 0,05. Ada pengaruh regulasi emosi terhadap resiliensi akademik bernilai rx1ysebesar 0.474 dengan p < 0.05, serta uji regresi berganda dengan hasil 0,000 < 0,05.Kata Kunci: Regulasi Emosi, Dukungan Sosial Keluarga, Resiliensi Akademik